PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN CALON PASANGAN PENGANTIN DI KANTOR URUSAN AGAMA KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Bahri, Hanifa; Uceng, Andi; Adnan, Andi Astinah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The Influence of Service Quality on the Satisfaction of Prospective Marriage Couples at the Office of Religious Affairs (KUA) in Baranti District, Sidenreng Rappang Regency. (Supervised by Mr. Andi Uceng andMrs.Hj.A.AstinahAdnan). The purpose of this research is to determine the influence of service quality on the satisfaction of prospective marriage couples at the Office of Religious Affairs (KUA) in Baranti District, Sidenreng Rappang Regency. This study uses a quantitative descriptive approach. The population in this research consisted of 197 prospective marriage couples who visited KUA Baranti. The sample size was 131 respondents, determined using the Slovin formula and random sampling technique. The data collection techniques used in this research were observation, interviews, literature review, and questionnaires. The collected data were processed and analyzed using quantitative descriptive analysis with the help of IBM SPSS Statistics25. Based on the data analysis, the research findings show that Variable X (Service Quality) obtained a total percentage of 84.44%, categorized as very satisfied; Variable Y (Couples’ Satisfaction) received a total percentage of 81.47%, also categorized as very satisfied; and the overall influencing factors achieved a percentage of 82%, falling into the very satisfied category.